Reduction of symmetric semidefinite programs using the regular representation - Klerk, Etienne de. (2012)
We consider semidefinite programming problems on which a permutation group is acting.We describe a general technique to reduce the size of such problems, exploiting the symmetry. The technique is based on a low-order matrix ∗-representation of the commutant (centralizer ring) of the matrix algebra generated by the permutation matrices.We apply it to extending amethod of de Klerk et al. that gives a semidefinite programming lower bound to the crossing number of complete bipartite graphs. It implies that cr(K8,n) ≥ 2.9299n2−6n, cr(K9,n) ≥ 3.8676n2 − 8n, and (for any m ≥ 9) lim n→∞ cr(Km,n)/Z(m, n) ≥ 0.8594 m/m − 1, where Z(m,n) is the Zarankiewicz number [1/4(m-1)2][1/4(n-1)2], which is the conjectured value of cr(K m,n ). Here the best factor previously known was 0.8303 instead of 0.8594.